Two strategies study of dialogue in ukrainian psychology (Pedagogy of Higher and Secondary Education, 2013)
Dyakonov G.V.Two strategies study of dialogue in ukrainian psychology.In the article two strategies of research of dialog open up in Ukrainian psychological science: activity-genetics (incarnate in works of representatives of scientific school of G.S.Kostyuk) and actionally-ontological (realized in labours of scientific school of V. A. Romenec).
Keywords: dialogue; dialogic approach-genetic strategy; development and selfdevelopment of personality